Phase II study to evaluate combining gemcitabine with flutamide in advanced pancreatic cancer patients - Corrie, P (Nature Publishing Group, 2002)
A phase II study was undertaken to determine the safety of combining flutamide with gemcitabine, with response rate being the primary end point. Twenty-seven patients with histologically proven, previously untreated, unresectable pancreatic adenocarcinoma received gemcitabine, 1 g m(−2) intravenously on days 1, 8 and 15 of a 28 day cycle, and flutamide 250 mg given orally three times daily. Treatment was halted if there was unacceptable toxicity, or evidence of disease progression. Toxicity was documented every cycle. Tumour assessment was undertaken after cycles 2 and 4, and thereafter at least every additional four cycles. One hundred and seventeen cycles of treatment were administered, median four cycles per patient (range 1–18). Gemcitabine combined with flutamide was well tolerated, with most toxicities being recorded as grade 1 or 2 and only nine treatment cycles associated with grade 3 toxicity. The most frequent toxicity was myelosuppression. One case of transient jaundice was recorded. The commonest symptomatic toxicity was nausea and vomiting. The response rate was 15% (four partial responses), median survival 6 months and 22% of patients were alive at 1 year. These results suggest antitumour activity of the combination therapy to be equivalent to single agent gemcitabine. British Journal of Cancer (2002) 87, 716–719. doi:10.1038/sj.bjc.6600523 www.bjcancer.com © 2002 Cancer Research UK